2022
DOI: 10.3390/molecules27072068
|View full text |Cite
|
Sign up to set email alerts
|

Chemometric Classification of Colombian Cacao Crops: Effects of Different Genotypes and Origins in Different Years of Harvest on Levels of Flavonoid and Methylxanthine Metabolites in Raw Cacao Beans

Abstract: The aim of this study was to evaluate the levels of chemical markers in raw cacao beans in two clones (introduced and regional) in Colombia over several years. Multivariate statistical methods were used to analyze the flavanol monomers (epicatechin and catechin), flavanol oligomers (procyanidins) and methylxanthine alkaloids (caffeine and theobromine) of cocoa samples. The results identified genotype as the main factor contributing to cacao chemistry, although significant differences were not observed between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
1
0
1
Order By: Relevance
“…For their part, Tee et al (18) found in their research that ripe cocoa fruits produce beans with a higher content of flavonoids, catechins, and total phenols, managing to produce a chocolate with the highest score in flavor intensity and complexity and the lowest in acidity and astringency. Finally, Agudelo et al (19) and Oracz and Nebesny (20) confirmed the effect of different genotypes and geographical locations in various harvest years on the content of some metabolites (total polyphenol content, antioxidant capacity, and metal chelating activity) in cocoa beans.…”
Section: Introductionmentioning
confidence: 85%
“…For their part, Tee et al (18) found in their research that ripe cocoa fruits produce beans with a higher content of flavonoids, catechins, and total phenols, managing to produce a chocolate with the highest score in flavor intensity and complexity and the lowest in acidity and astringency. Finally, Agudelo et al (19) and Oracz and Nebesny (20) confirmed the effect of different genotypes and geographical locations in various harvest years on the content of some metabolites (total polyphenol content, antioxidant capacity, and metal chelating activity) in cocoa beans.…”
Section: Introductionmentioning
confidence: 85%
“…Some papers will be discussed in more detail below as illustrative examples. Using the content of catechins, some procyanidins, and xanthines, as well as unknown but quantitatively relevant peaks recorded by HPLC-UV, Agudelo et al explored the possibility of distinguishing among Colombian samples collected in different years belonging to introduced and autochthonous clones [ 75 ]. PCA results showed some structuration according to these features, but some class overlapping also occurred.…”
Section: Profiling-based Authenticationmentioning
confidence: 99%
“…El cultivo de cacao en Colombia juega un rol económico relevante considerándose como un sector empresarial estratégico (Agudelo et al, 2022), donde el 95% de su producción es considerada por la Organización Internacional del Cacao (ICCO) como "cacao fino". Esta producción es generada por un selecto grupo de países y es bastante apetecida en el mercado internacional, caracterizándose principalmente por su sabor, que es el resultado de factores intrínsecos de la planta, como de factores externos asociados al proceso de cultivo, siembra y procesamiento (ICCO, 2022a).…”
Section: Importancia Nacional Del Cacaounclassified